Intelligent audio production strategies informed by best practices - Pestana, Pedro Duarte (2016)
The main focus of this article is to explore and investigate the fundamental constraints that should be at the basis of algorithm development in intelligent audio production systems. Through mix analysis and grounded theory strategies, a best-practices framework on the craft of mixing is sought out. Findings, while not to be taken as dogmatic, give a clear indication of preferred implementation strategies, and show what still needs to be done to fully understand the technical choices that audio mixing has incorporated throughout its history.